Hocus pocus! : tricks for amateur magicians : 4D a magical augmented reading experience - Barnhart, Norm (Amazing magic tricks., 2018)
"Describes how to prepare and perform several magic tricks for apprentice level magicians. Includes embedded links for added online instructional videos that can be accessed with the Capstone 4D app"--